Unequal physical activity among children with cerebral palsy in Sweden—A national registry study. Issue 3 (9th August 2021) - Degerstedt, Frida; Björklund, Martin; Keisu, Britt‐Inger; Enberg, Birgit
Abstract: Aim: To examine the extent to which sex, country of birth, and functional aspects influence participation in physical education and physical leisure activity among children with cerebral palsy (CP) in Sweden. Methods: This national cross‐sectional registry study included children with CP aged 6 to 18 years who participated in the Swedish national quality registry, the Cerebral Palsy Follow‐up Program, CPUP, in 2015. Comparisons and associations between sex, country of birth, and functional aspects and physical leisure/physical education were examined using chi‐squared and multivariable logistic regression analysis. Results: The study included 1935 children. Of them, 1625 (87%) reported participating in physical education and 989 (53%) reported participating in physical leisure activity. Children born in Sweden had higher odds of participating in physical education (OR: 1.99; 95% CI: 1.20‐3.28) and physical leisure activity (OR: 2.51; 95% CI: 1.70‐3.72) compared with children born outside Europe. Greater impairment of gross motor function was associated with lower participation levels. Boys participated slightly more frequently in leisure activities than girls. Conclusion: Enhancing social inclusion with regard to disability, birth country, and sex are important and achievable goals for policymakers and practitioners for promoting participation in physical activity for children and adolescents with CP.